The importance of preventing risk factors in stroke: integrative literature review (Research, Society and Development, 2021)
The cerebrovascular accident (CVA) is a disease characterized by a functional neurological impairment, involving the central nervous system resulting in a circulation disorder. The same can be qualified as ischemic, when there is obstruction of blood vessels or hemorrhagic caused by the rupture of a blood vessel. The objective is to emphasize the importance of preventing risk factors in Stroke, based on an integrative literature review. The research focused on a perspective of integrative literature review methods. Data collection of articles in the literature was performed a search in the following databases: Latin American and Caribbean Literature in Health Sciences (LILACS) and Online Medical Literature Analysis and Retrieval Sistem (Medline), Academic Google and Scielo. The risk of stroke begins to increase over the years. Among the main risk factors, there are non-modifiable factors which are: heredity, sex and ethnicity, with males and blacks having a higher incidence of stroke ischemic. As for modifiable risk factors, hypertension is classified, being the main one, which causes an increase of more than three times in the incidence in cases of stroke. It is concluded that early diagnosis ensures greater minimization of harm to the patient and is also the responsibility of the health team and nurses.